Dual Energy X-Ray Absorptiometry Analysis of Broiler Breeder Eggs for Prediction of Egg Components and Evaluation of Egg Shell Quality - England, J.A.; Salas, C.; Ekmay, R.D.; Coon , C.N. (International Journal of Poultry Science, 2012)
Most methods for evaluating shell quality and egg components are destructive and time consuming. Four trials were conducted to investigate the use of Dual Energy X-ray Absorptiometry (DXA) as a fast and non-destructive method for evaluating shell quality and measuring the components of broiler breeder eggs. In Trial 1, 180 eggs were scanned with a GE Lunar Prodigy DXA. The eggs were also evaluated by traditional methods that required breaking the eggs for shell quality evaluation and egg components (shell, albumen and yolk) weighed. Values obtained from the DXA scans were subjected to stepwise regression analysis to develop prediction equations. Prediction equations were developed for the weight of egg components (egg, yolk, albumen and shell) and parameters of shell quality (shell weight, thickness and calcium content). In Trial 1, the r2 values for the prediction equations using DXA values were 0.9961, 0.9692, 0.9843, 0.6891, 0.8499 and 0.5738 for the total egg weight, shell weight, shell calcium content, shell thickness, albumen weight and yolk weight, respectively (P>F, F,